The relationship between social and environmental factors and symptom severity in the seriously mentally ill population. (February 2022) - Von Mach, Tara; Rodriguez, Katrina; Mojtabai, Ramin; Spivak, Stanislav; Eaton, William W; Cullen, Bernadette A
Background: The goal of this article is to investigate the relationship of psychiatric symptom severity with internalised stigma, neighbourhood environment, and social support among individuals with serious mental illness. Method: Using a longitudinal study design we examined the relationship between psychiatric symptom severity with internalised stigma, neighbourhood environment, and social support among 271 adults with serious mental illness recruited from new admissions to two urban mental health clinics. Results: After controlling for demographics increased stigma levels predicted greater symptom severity, as measured by the Positive and Negative Syndrome Scale (PANSS) Positive, Negative, and General Psychopathology scales over a 4-year period ( p  < .05). In adjusted models, individuals who reported living in more disadvantaged neighbourhoods also reported higher PANSS Negative and General scores over time ( p  < .05). Social support from friends and relatives was not significantly related to PANSS Positive, Negative, or General Psychopathology scores among individuals with serious mental illness. Conclusions: Individuals with serious mental illness who experience internalised stigma and neighbourhood disadvantage experience greater symptom severity over time. Targeting stigma and housing during treatment could potentially impact symptom severity in this population.